PENERAPAN KEADILAN RESTORATIF DALAM PENYELESAIAN KASUS VAKSIN KOSONG - Apriliansyah (2022)
Criminal law is a rule that must be obeyed in a country as a form of obligation to enforce the law, contains prohibitions that are contrary to the law and provides a punishment for each person the prohibition. Criminal law cannot be separated from punishment, punishment is a form of responsibility that must be carried out by perpetrators who commit criminal acts or also known as retributive theory. In the criminal justice system in Indonesia, the settlement of criminal cases through the courts and the theory of punishment (retributive), often creates problems and negative impacts. Thus, an approach that focuses on out-of-court settlements emerged, namely the Restorative Justice approach. By using normative juridical research methods, the author will discuss how the position of restorative in the legal system in Indonesia and the application of restorative justice, especially at the investigation stage. To support the research, the author uses data collection techniques through library research with a statute approach and case approach related to Restorative Justice.